IPTEKS PENGELOLAAN PIUTANG PADA DEPARTEMEN SERVIS DI PT. ASTRA INTERNATIONAL ISUZU SALES OPERATION CABANG MANADO - Mangayuk, Elma Natasha; Pusung, Rudy J. (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
PT Astra Isuzu is part of Astra's automotive group. In carrying out its business, the company has three departements namely unit sales departement, service departement, and spare part sales departement. This research is about managing receivables in the service departement at PT Astra Isuzu, Manado branch. In the service department of PT Astra Isuzu the Manado branch has five types of customers. therefore the company must pay attention to several things in managing its receivables according to the type of customer who has obligations. There are three stages that must be carried out by the company in managing its receivables in order to avoid uncollectible receivables, namely the company must know the condition of the cause of the receivables, the company must understand the administrative process, and must ensure the repayment of the accounts. PT Astra Isuzu also makes a account receivable protection policy for customers who are always late in paying their obligations. In this case, PT Astra Isuzu Manado branch is good enough in managing its service receivables, but the company needs to pay more attention to the division of tasks specifically in terms of collection of receivables.Keywords : Receivables, Managing Receivables, Account Receivable Protection